ULTRA-SHORT PRESENTATION IN VIRTUAL ENGLISH PUBLIC SPEAKING OF NON-ENGLISH MAJOR STUDENTS - Hilaliyah, Iil; Zaitun, Zaitun (Jurnal Kajian Pembelajaran dan Keilmuan, 2024)
This research is aimed to introduce one technique of performing English public speaking to non-English major students called Ultra-Short Presentation. There were a number of 34 non-English students of Faculty of Education, Universitas Muhammadiyah Jakarta, participated in this study, registered as the second semester in the academic year of 2022/2023. The method applied in this study was quantitative approach with true experimental design. In collecting the data, both pre and post-tests of performing public speaking virtually were used. Each student"™s English public speaking performance was assessed by using scoring rubric for public speaking covering three facets; the introduction, the middle, the conclusion. This assessment consisted from "˜excellent"™ to "˜very poor"™ criterions. The analysis data of one-group pretest-post-test design revealed that the students performed better in the post-test than in the pre-test in which the average score they obtained in this test was 61.4, while in the post-test was 82.3. Besides, among the three parts assessment, the students reached their highest performance in the introduction section, while the lowest achievement was in the middle. These results confirmed that Ultra-Short Presentation was effective in making English public speaking of non-English major students more effective.